Antibacterial MACS nano material and preparation method thereof
By developing a triple antibacterial MACS nanomaterial based on photothermal therapy, chemodynamic therapy and thermodynamic therapy, combined with near-infrared laser, the problem of limited effectiveness of existing antibacterial agents on multidrug-resistant bacteria and biofilms protecting bacteria is solved, and efficient antibacterial effects and good biosafety are achieved.
Patent Information
- Application Number
- CN202411700463.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing antibacterial agents have limited effects when facing multidrug-resistant bacteria and biofilm-protected bacteria and may induce multidrug-resistant resistance.
A triple antibacterial MACS nanomaterial based on photothermal therapy (PTT), chemodynamic therapy (CDT) and thermodynamic therapy (TDT) is developed to generate bactericidal substances such as ·OH and R· through a combination of mesoporous polydopamine (MPDA) nanoparticles, 2,2′-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride (AIPH) and copper peroxide (CuO2) nanoparticles, combined with near-infrared lasers, generate bactericidal substances such as ·OH and R· to destroy biofilms and effectively kill bacteria.
It has achieved effective killing of multidrug-resistant bacteria and biofilm-protected bacteria, significantly improved the antibacterial effect, and has good in vivo biosafety and industrial application potential.
Smart Images

Figure CN119700705A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial materials, in particular to an antibacterial MACS nano material and a preparation method thereof. Background Art
[0002] Infections caused by pathogenic bacteria can induce a variety of diseases and complications, and have become a common health problem in modern medicine, posing a serious threat to human health. Currently, antibiotic drugs are a widely used strategy to combat bacterial infections. However, overuse of antibiotics can lead to the formation of multidrug-resistant bacteria, making it more difficult to combat bacterial infections. In addition, bacteria can also protect themselves from harsh conditions or drug attacks by forming biofilms. The protective matrix, composed of polysaccharides, proteins, and extracellular DNA, serves as a refuge for bacteria, hindering the spread of antimicrobial agents, and resistance genes can spread in bacteria wrapped in biofilms through horizontal gene transfer, thereby exacerbating bacterial resistance. Therefore, there is an urgent need to develop effective alternative strategies to treat biofilm-associated bacterial infections without inducing multidrug resistance.
[0003] In recent years, photothermal therapy (PTT) induced by near-infrared (NIR) light has attracted wide attention in anti-infection treatment due to its low invasiveness and few side effects. High temperature can destroy the structure of biofilm by inactivating its inherent bioactive matrix (such as nucleic acids and proteins), thereby promoting the penetration of antimicrobial agents and killing bacteria protected by biofilm. Single-modality PTT is usually performed using high-power density NIR lasers and long-term exposure. Limited by insufficient targeting specificity and the penetration depth of excitation light, its therapeutic effect is limited and may damage normal tissues. Therefore, the synergistic treatment strategy combining PTT with other technologies such as chemodynamic therapy (CDT), photodynamic therapy (PDT), sonodynamic therapy (SDT), nanozymes, etc. has received widespread attention in combating pathogenic bacterial infections and even biofilm-related diseases. Summary of the invention
[0004] The invention provides an antibacterial MACS nanomaterial and a preparation method thereof, and prepares a triple antibacterial MACS nanomaterial based on PTT / CDT / TDT, which has better contact with bacteria and has good antibacterial and anti-biofilm effects.
[0005] The technical solution of the present invention is achieved as follows: an antibacterial MACS nanomaterial comprises a core, carboxymethyl chitosan is encapsulated on the outside of the core, the core comprises mesoporous polydopamine (MPDA) nanoparticles, and the mesoporous polydopamine nanoparticles are loaded with 2,2′-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride (AIPH) and copper peroxide (CuO2) nanoparticles.
[0006] Furthermore, the particle size of the CuO2 nanoparticles is 5-15 nm, and the particle size of the antibacterial MACS nanomaterials is 100-150 nm.
[0007] Furthermore, the encapsulation efficiency of AIPH was 50%-60%.
[0008] A method for preparing an antibacterial MACS nanomaterial comprises the following steps:
[0009] (1) adding mesoporous polydopamine nanoparticles and AIPH to water, stirring for 10-14 hours in the dark, and then adding CuO2 nanoparticles, stirring for 2-5 hours to obtain a core;
[0010] (2) Adding the core and carboxymethyl chitosan into water and stirring for 12-24 hours to obtain antibacterial MACS nanomaterials.
[0011] Furthermore, in step (1), the mass ratio of the mesoporous polydopamine nanoparticles to the AIPH is 1:0.5-1, and the mass ratio of the mesoporous polydopamine nanoparticles to the CuO2 nanoparticles is 3:1-3.
[0012] Furthermore, in step (2), the mass ratio of the core to the carboxymethyl chitosan is 1:3-10.
[0013] Furthermore, in step (1), the preparation method of mesoporous polydopamine nanoparticles is as follows:
[0014] Pluronic F127 and dopamine hydrochloride were added to an ethanol aqueous solution with a volume concentration of 50%, and stirred at room temperature until the solution became clear; then, 1.0 mL of mesitylene (TMB) was injected under stirring conditions, and after stirring for 30 minutes, concentrated ammonia was dripped in to induce self-polymerization of dopamine oligomers. After continuous reaction for 10-15 hours, the mixture was centrifuged and washed to obtain mesoporous polydopamine nanoparticles with uniform particle size.
[0015] Furthermore, the preparation method of CuO2 nanoparticles is as follows: PVP is dissolved in a CuCl2·2H2O aqueous solution, and then NaOH and H2O2 are added in sequence, and after stirring for reaction, ultrafiltration and washing are performed to obtain CuO2 nanoparticles.
[0016] Furthermore, the mass ratio of Pluronic F127 to dopamine hydrochloride is 2:1, and the mass concentration of concentrated ammonia water is 25%.
[0017] Beneficial effects of the present invention:
[0018] The antibacterial MACS nanomaterial prepared by the present invention fights against bacterial infection by combining light and heat with self-supplied hydrogen peroxide to produce OH and oxygen-independent R. When MACS accumulates at the infection site or biofilm, the acidic microenvironment triggers the charge of the outer layer of carboxymethyl chitosan of the material to change from negative to positive, attracting the negatively charged bacteria at the infection site and thus better contacting the bacteria. In addition, the acidic environment can also trigger the Cu in the material to 2+ and H2O2 co-release, Cu 2+ The self-supplied H2O2 was converted into ·OH by catalysis through a Fenton-like reaction. In addition, with the help of 808nm near-infrared laser, the high heat caused by MPDA induced the decomposition of AIPH to generate R·. Therefore, MACS synergizes PTT, CDT and TDT and has stronger contact with bacteria, making it have good antibacterial and anti-biofilm effects, outstanding therapeutic effects on subcutaneous infection abscesses, and good in vivo biosafety.
[0019] The antibacterial MACS nanomaterial prepared by the present invention has a regular morphology, uniform nanoparticle size, uniform dispersion, low material price, reduced cost, and good antibacterial effect. With the help of near-infrared laser, the MACS nanomaterial has an antibacterial rate of 99.9% against Staphylococcus aureus and MRSA at a concentration of 150 μg / mL, which indirectly indicates that the drug resistance of MRSA to MACS is invalid. At the same time, for Escherichia coli, the MACS concentration needs to be increased to 200 μg / mL to achieve a similar antibacterial rate, which may be related to the complex cell wall composition of Escherichia coli.
[0020] The preparation method of the invention is simple, mild, efficient, economical and affordable, suitable for large-scale industrial application and promotion, and meets the requirements of environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 It is a schematic diagram of the preparation process of the nano antibacterial material MACS involved in the present invention;
[0023] Figure 2 This is the transmission electron microscope image of CuO2;
[0024] Figure 3 is the scanning electron micrograph of MACS;
[0025] Figure 4 It is the photothermal performance diagram of MACS;
[0026] Figure 5 It is the chemodynamic therapy performance diagram of MACS;
[0027] Figure 6 The photothermal-enhanced chemodynamic therapy performance diagram of MACS;
[0028] Figure 7 It is the thermodynamic therapy performance diagram of MACS;
[0029] Figure 8 This is a plate picture of the antibacterial performance of MACS at different concentrations;
[0030] Fig. 9 It is a flat plate picture of the antibacterial properties of different nanoparticles;
[0031] Fig.10 It is the result of MACS biocompatibility test on various cells;
[0032] Fig.11 is a transmission electron microscopy image of the MPDA nanoparticles prepared in Example 1;
[0033] Fig.12 It is the encapsulation efficiency diagram of AIPH at different mass ratios of MPDA and AIPH. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] like Figure 1 As shown, a method for preparing an antibacterial MACS nanomaterial comprises the following steps:
[0037] Synthesis of MPDA nanoparticles: prepare 100 mL of a mixed solution of water and ethanol, wherein the volume ratio of water to ethanol is 1:1, weigh F127 and dopamine hydrochloride (mass ratio of 2:1) and dissolve them in the mixed solution, and vigorously stir at room temperature to obtain a clear solution; then slowly inject 1.0 mL of TMB at a stirring speed of 500 rpm to form a nanoemulsion system, and after stirring for 30 minutes, drop 5 mL of concentrated ammonia (mass fraction 25%) into the above mixture to induce self-polymerization of dopamine oligomers; after continuous reaction for 12 hours, centrifuge the formed mesoporous TMB / F127 / PDA polymer nanosphere product, wash with water and ethanol three times in sequence to obtain MPDA nanoparticles.
[0038] Synthesis of CuO2 nanoparticles: 2.5 g PVP was dissolved in CuCl2·2H2O aqueous solution (25 mL 0.01 M), and then NaOH (25 mL 0.02 M) and 30% H2O2 (500 μL) were added in sequence. After stirring for 30 minutes, the CuO2 nanoparticles were collected by ultrafiltration and washed with water three times.
[0039] The obtained MPDA nanoparticles and AIPH were added to an aqueous solution at a mass ratio of 1:1, wherein the final concentration of AIPH was 2 mg / mL, and after stirring for 12 hours in a dark place, CuO2 nanoparticles were added and stirring was continued for 3 hours, and finally washed with water to obtain a core, which was a mesoporous polydopamine (MAC) loaded with AIPH and CuO2 at the same time, and the core was freeze-dried and set aside;
[0040] MAC and carboxymethyl chitosan were added to the aqueous solution in a mass ratio of 1:3, ultrasonically dissolved, and stirred at room temperature for 24 hours. After the reaction, the MACS nanomaterials were washed three times with deionized water and freeze-dried.
[0041] Example 2
[0042] This embodiment is basically the same as embodiment 1, except that MPDA nanoparticles and AIPH are added to the aqueous solution at a mass ratio of 1:0.5.
[0043] Example 3
[0044] This embodiment is basically the same as Embodiment 1, except that the obtained MPDA nanoparticles and AIPH are added to the aqueous solution at a mass ratio of 1:0.8.
[0045] The CuO2 nanoparticles and MACS nanomaterials prepared in Example 1 were characterized and tested for performance, as follows:
[0046] The CuO2 nanoparticles were dispersed on a copper grid and observed using a transmission electron microscope. Figure 2As shown, the prepared CuO2 nanoparticles have a uniform particle size of about 5-15 nm;
[0047] The MACS nanomaterials were dispersed on a silicon wafer and observed using a scanning electron microscope after gold spraying. Figure 3 As shown, MACS is evenly distributed, regular in shape, and has a particle size of approximately 100-150 nm.
[0048] Photothermal performance test of MACS nanomaterials
[0049] MACS can convert light energy into heat energy under 808nm near-infrared irradiation. This property is called photothermal performance. Therefore, the heating effect of MACS can be detected by detecting the temperature change of MACS under 808nm light. The specific operation steps are as follows: Disperse MACS in deionized water to form dispersions of different concentrations, take 1mL in an EP tube and irradiate with 808nm laser (1.5W / cm 2 ) for 10 minutes, and use an electronic thermometer to measure and record the temperature every half minute. Figure 4 As shown, the dispersion with a concentration of 0 as a control has no obvious photothermal effect, and the temperature does not rise significantly after 10 minutes of illumination. The temperature of the dispersion with a concentration of 200 μg / mL rises from 27°C to 53.9°C after 10 minutes of illumination. This proves that MACS nanomaterials have good photothermal conversion performance.
[0050] Chemodynamic Therapy Performance Testing of MACS Nanomaterials
[0051] MACS can decompose under weak acidic conditions to produce hydrogen peroxide and Cu 2+ , followed by hydrogen peroxide and Cu 2+ The ability of MACS to generate hydroxyl radicals (·OH) was evaluated by measuring the absorbance of MB (methylene blue) at 665nm, which can be effectively degraded by ·OH, using a Fenton-like reaction. In pH 5.5 buffer, MACS nanocomposites of different concentrations (0, 50, 100, 200, 400 μg / mL) were added to PBS buffer (pH 5.5) containing MB (5 mg / mL 10 μL) and reacted in the dark for 30 minutes. Then centrifugation (8000 rpm, 5 min) was performed to remove the residual MACS, and the absorbance of the supernatant at 665nm was detected by UV-2550 spectrophotometer. The results are shown in Figure 2. Figure 5 As shown, under the condition of pH 5.5, the peak at 665 nm was significantly reduced compared with the control group, indicating that MACS nanomaterials can undergo a Fenton-like reaction to generate ·OH in an acidic microenvironment (pH 5.5).
[0052] In pH 5.5 buffer, 200 μg / mL of MACS nanocomposite was added to PBS buffer (pH 5.5) containing MB (5 mg / mL 10 μL), one group was irradiated with 808 near-infrared laser for 10 min, and then the absorbance of the supernatant at 665 nm was detected by UV-2550 spectrophotometer. Figure 6 As shown in Figure 5, under near-infrared irradiation, the peak at 665 nm is significantly reduced compared with the control group, indicating that photothermal can promote the material to generate more ·OH.
[0053] MACS Testing of Thermodynamic Therapeutic Performance of Nanomaterials
[0054] In order to study the decomposition of AIPH under thermal stimulation, 2,2′-azobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) was used as a detection probe, which can react with free AIPH radicals to generate green ABTS. + The solution was treated with UV spectrophotometer to measure the absorption peak at different near-infrared irradiation times. Figure 7 As shown in the figure, there was no change in the control group (ultrapure water) and the ABTS plus light group alone. As the light exposure time increased, the ABTS generated by the MACS nanomaterials + The more the absorbance, the higher the value. The results show that MACS nanomaterials can decompose AIPH through thermal stimulation to release the bactericidal substance R·.
[0055] Antibacterial properties of MACS nanomaterials at different concentrations
[0056] Gram-positive Staphylococcus aureus (S. aureus), Gram-negative Escherichia coli (E. coli) and methicillin-resistant Staphylococcus aureus (MRSA) were selected as model strains. Different concentrations of drugs were mixed with fresh bacterial suspension (1×10 6 CFU / mL). The mixture was then divided into two groups: 2 ,10min) (with NIR) and without laser irradiation (withnot NIR). 100μL of the above treated suspension was evenly spread on the agar plate in each group. After culturing in a 37℃ constant temperature incubator for 16h, the number of colonies on the agar plate was counted. The results are shown in Figure 8As shown in the figure, at the same concentration, the number of colonies in the near-infrared treatment group was significantly lower than that in the non-near-infrared treatment group. In addition, as the concentration of MACS increased, the number of bacterial colonies decreased significantly. At a concentration of 150 μg / mL, the antibacterial rate of MACS against Staphylococcus aureus and MRSA reached 99.9%, indirectly indicating that MRSA's resistance to MACS was ineffective. At the same time, for E. coli, the MACS concentration needed to be increased to 200 μg / mL to achieve a similar antibacterial rate, which may be related to the complex cell wall composition of E. coli.
[0057] Different materials were mixed with fresh bacterial suspension (1×10 6 CFU / mL) was mixed, with a material concentration of 150 μg / mL for Staphylococcus aureus and MRSA, and a material concentration of 200 μg / mL for Escherichia coli. The mixture was then divided into two groups: 2 , 10min) (with NIR) and without laser irradiation (withnotNIR). 100μL of the above-treated suspension was evenly spread on the agar plate in each group. After culturing in a 37℃ constant temperature incubator for 16h, the number of colonies on the agar plate was counted. The results are shown in Fig. 9 As shown, the PBS control group (Control) did not cause significant damage to the three strains. MPDA (abbreviated as: MP) showed low toxicity to the three strains, while the MPDA+NIR group had certain antibacterial activity (PTT). When AIPH, CuO2 and MPDA were used in combination (core, MAC), in the absence of near-infrared, it killed nearly half of Staphylococcus aureus. With the help of near-infrared laser, MAC almost completely killed Staphylococcus aureus, indicating that the antibacterial effect of MAC combined with near-infrared was significant. The antibacterial activity of MACS against Staphylococcus aureus was more than half that of MAC, indicating that carboxymethyl chitosan also has certain antibacterial properties. The antibacterial rate of the MACS+NIR treatment group was 100%. Similar antibacterial results were also observed for Escherichia coli and methicillin-resistant Staphylococcus aureus. These results strongly indicate that MACS has good antibacterial properties under 808nm near-infrared laser irradiation.
[0058] Biocompatibility of MACS nanomaterials with various cells
[0059] The CCK-8 method was used to evaluate the cytotoxicity of MACS nanomaterials on mouse embryonic fibroblasts (NIH-3T3), human umbilical vein endothelial cells (HUVEC) and cervical cancer cells (Hela). 5Cells were incubated at 37°C in a 5% CO2 incubator for 24 h and treated with different concentrations of MACS nanomaterials for 24 and 72 h. After treatment, the cells were washed three times with sterile PBS and fresh culture medium containing CCK8 reagent (100 μL) was added each time. The cells were incubated at 37°C for 4 h and the absorbance at 495 nm was measured for each well. The results are shown in Fig.10 As shown, when the concentration of MACS nanomaterials reached 200 μg / mL, the survival rate of the three cells remained above 80%. The results showed that MACS nanomaterials have good biocompatibility.
[0060] In summary, the MACS nanomaterial prepared by the present invention has excellent antibacterial properties, good safety, high biocompatibility, low required concentration, and spectral bactericidal effect, and can be used to prepare antibacterial drugs.
[0061] Comparative Example 1
[0062] This example is basically the same as Example 1, except that concentrated ammonia is dripped into the above mixture to induce dopamine oligomer self-polymerization. After continuous reaction for 30 minutes, the formed mesoporous TMB / F127 / PDA polymer nanosphere product is centrifuged, washed with water and ethanol three times in sequence to obtain MPDA nanoparticles.
[0063] The centrifugal results showed that the product was small in amount and had a low yield. The product was observed to have many impurities under transmission electron microscopy and the particle size was not uniform.
[0064] In Example 1 of the present application, the continuous reaction time was extended to 12 hours, and the product obtained by centrifugation increased significantly, and the yield was improved. Through transmission electron microscopy, impurities disappeared from the product, and the nanoparticles had uniform particle sizes.
[0065] The MPDA nanoparticles prepared in Example 1 were dispersed on a copper mesh and observed using a transmission electron microscope. Fig.11 As shown: Transmission electron microscopy results show that the prepared MPDA nanoparticles have a uniform particle size of about 90-120nm.
[0066] Comparative Example 2
[0067] This embodiment is basically the same as embodiment 1, except that the obtained MPDA nanoparticles and AIPH are added to the aqueous solution at a mass ratio of 1:1.5.
[0068] Comparative Example 3
[0069] This embodiment is basically the same as Embodiment 1, except that the obtained MPDA nanoparticles and AIPH are added to the aqueous solution at a mass ratio of 1:2.
[0070] Depend on Fig.12It can be seen that the mass ratio of MPDA nanoparticles to AIPH affects the encapsulation efficiency of AIPH. When the mass ratio of MPDA to AIPH is 1:0.5-1, the encapsulation efficiency of AIPH is 50%-60%.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial MACS nanomaterial, characterized in that: The invention comprises a core, the outer side of the core is encapsulated with carboxymethyl chitosan, the core comprises mesoporous polydopamine nanoparticles, and the mesoporous polydopamine nanoparticles are loaded with AIPH and CuO2 nanoparticles.
2. The antibacterial MACS nanomaterial according to claim 1, characterized in that: The particle size of CuO2 nanoparticles is 5-15nm, and the particle size of antibacterial MACS nanomaterials is 100-150nm.
3. An antibacterial MACS nanomaterial according to claim 1 or 2, characterized in that: The encapsulation efficiency of AIPH was 50%-60%.
4. The method for preparing an antibacterial MACS nanomaterial according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) adding mesoporous polydopamine nanoparticles and AIPH to water, stirring for 10-14 hours in the dark, and then adding CuO2 nanoparticles, stirring for 2-5 hours to obtain a core; (2) Adding the core and carboxymethyl chitosan into water and stirring for 12-24 hours to obtain antibacterial MACS nanomaterials.
5. The preparation method according to claim 4, characterized in that: In step (1), the mass ratio of mesoporous polydopamine nanoparticles to AIPH is 1:0.5-1, and the mass ratio of mesoporous polydopamine nanoparticles to CuO2 nanoparticles is 3:1-3.
6. The preparation method according to claim 4, characterized in that: In step (2), the mass ratio of the core to the carboxymethyl chitosan is 1:3-10.
7. The preparation method according to claim 4 or 5, characterized in that: In step (1), the preparation method of mesoporous polydopamine nanoparticles is as follows: Pluronic F127 and dopamine hydrochloride were added to an ethanol aqueous solution with a volume concentration of 50%, and stirred at room temperature until the solution became clear; then, 1.0 mL of mesitylene was injected under stirring conditions, and after stirring for 30 minutes, concentrated ammonia was dripped in to induce self-polymerization of dopamine oligomers. After continuous reaction for 10-15 hours, the mixture was centrifuged and washed to obtain mesoporous polydopamine nanoparticles with uniform particle size.
8. The preparation method according to claim 4 or 6, characterized in that: The preparation method of CuO2 nanoparticles is as follows: PVP is dissolved in a CuCl2·2H2O aqueous solution, and then NaOH and H2O2 are added in sequence, and after stirring for reaction, ultrafiltration and washing are performed to obtain CuO2 nanoparticles.
9. The preparation method according to claim 7, characterized in that: The mass ratio of Pluronic F127 to dopamine hydrochloride is 2:1, and the mass concentration of concentrated ammonia water is 25%.
Citation Information
Patent Citations
Near-infrared light response halloysite-based nano antibacterial composite material and preparation method thereof
CN116271023A
Mesoporous polydopamine / cuprous sulfide-polyethyleneimine nanocomposite as well as preparation method and application thereof
CN116920088A
Astragalus polysaccharide composite nanoparticle as well as preparation method and application thereof
CN118649148A
Table of Contents Memorization Learning System Using Keyword Image Interpreting
KR1020230029002A
Heat-resistant implantable polymer microneedle and preparation method therefor and application thereof
US20230173241A1